PENANGANAN PEKERJA SEKS KOMERSIAL DITINJAU DARI PERDA KOTA MEDAN NO 6 TAHUN 2003 TENTANG LARANGAN GELANDANGAN DAN PENGEMIS SERTA PRAKTEK TUNA SUSILA DI KOTA MEDAN - Ramadani Ramadani; Edy Ikhsan; Rosnidar Sembiring; Mirza Nasution (Universitas Sumatera Utara, 2018)
ABSTRACT The issuance of Perda Medan No. 6/2003 on the Prohibition of Bums, Beggars and Prostitution in Medan consisting of 7 articles is related to legal studies made and is aimed at realizing Medan to be Bestari city which is capable of handling prostitution in Medan. Prostitution is contradictory to religious and moral norms in the society in Medan. The number of prostitutes in Medan is still very high. Prostitutes are easily found at road sides of Medan from early evening until dawn. The policy made by Medan Municipality to overcome practice of prostitutes in Medan since 2003 is that it has issued a Perda (Regional Government Regulation). Medan Municipality coordinates with Social Agency of Medan and Polisi Pamong Praja (Civil Servant Police) Unit. The prostitutes caught in the raids are sent to Rehabilitation Center of Parawasa, Brastagi to implement the policy. The obstacles encountered by Medan Municipality to overcome prostitution in Medan consist of many factors such as the essence of the Perda. Other obstacles are contributed by the law enforcers whose work is not yet optimal; the law enforcement is influenced by internal and external factors. Keywords: Handling, Perda, PSK (Prostitution)